WOMEN'S LEADERSHIP STYLE AND MOTIVATION ON SHIP CHILD PERFORMANCE WITH WORK DISCIPLINE INTERVENING (Study on Ship Crew with Female Seafarers) - Mochamad Imroni Mubin; Tri Widayati; Hikmah Hikmah (Universitas 17 Agustus 1945 Semarang, 2023)
Leadership style plays a very important role in determining employee discipline because the leader can be used as an example and determinant for his subordinates. The style of a disciplined leader can affect the discipline of employees / subordinates. Another phenomenon is the provision of proper motivation, where it will be able to generate enthusiasm, passion and sincerity of work. The purpose of this study was to determine and analyze: 1) the influence of women's leadership style on work discipline, 2) the effect of work motivation on work discipline, 3) the influence of women's leadership styles on performance, 4) the effect of work motivation on performance, and 5) the effect of work discipline on performance. This type of research is causal associative quantitative with a survey approach. This research was conducted on a ship crew where there was a female leader/officer on the deck and the engine department with a total population of 60 people. The results showed 1) leadership style had a significant effect on work discipline, 2) work motivation had a significant effect on work discipline, 3) women's leadership style had a significant effect on performance, 4) work motivation had a significant effect on performance and 5) work discipline had significant effect on performance.